2021
DOI: 10.3389/fsufs.2021.638941
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Analysis (13C, 18O) of Wine From Central and Eastern Europe and Argentina, 2008 and 2009 Vintages: Differentiation of Origin, Environmental Indications, and Variations Within Countries

Abstract: In this study, we compare the stable isotope composition of oxygen and carbon of wines from four Central and Southeastern European countries and from Argentina to study the similarities and differences in the isotope signatures and, thus, the potential of differentiation of the various wine-growing countries. We observe similar trends for wines from Austria, Slovenia, and Romania with respect to the vintages 2008 and 2009, which are absent in the Montenegrin and Argentinean samples. It is speculated that the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…Since then each wine-producing EU-country produces each year a certain number of authentic wine samples, analyzes them for their IRMS and SNIF-NMR values and feeds these results into the database. Eventually, it was demonstrated that the wine data used for the control of authenticity could also be used for the control of the declared geographic origin [ 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The isotope and NMR-data is influenced by the ambient environmental conditions existing at the respective vineyards (also called terroir).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then each wine-producing EU-country produces each year a certain number of authentic wine samples, analyzes them for their IRMS and SNIF-NMR values and feeds these results into the database. Eventually, it was demonstrated that the wine data used for the control of authenticity could also be used for the control of the declared geographic origin [ 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The isotope and NMR-data is influenced by the ambient environmental conditions existing at the respective vineyards (also called terroir).…”
Section: Introductionmentioning
confidence: 99%
“…We assume that differentiation of wine from South Africa and Austria ( Figure S1 ) should be possible (for some indicative preliminary results see Christoph et al, 2015 [ 8 ]), without the need for annual reference samples for the exact definition of the vintage for differentiation (as the control of wine origin usually relies on the comparison of commercial samples with reference wine data of the same vintage), due to the difference in climatic conditions and the large geographical distance. Still, Horacek et al, 2021 [ 20 ], showed that wines of very different environments (Austria–Argentina) have overlapping isotope signatures, even though preliminary data by Christoph et al, 2015 [ 8 ], indicated no overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotope ratio analysis (SIRA) is arguably one of the most powerful tools for this purpose. This technique is already routinely applied for the control of authenticity of wine produced in EU countries [ 2 , 3 ] and has been proven to be successful for many other kinds of foodstuff [ 4 , 5 ]. Several studies on meat [ 6 ], such as lamb [ 7 , 8 ], pork [ 9 , 10 ], and chicken [ 11 ] have already been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The applied methods often depend on the commodity being investigated and include a stable isotope analysis of the main elements of biogenic materials (H, C, N, O, S), isotope analysis of heavy elements such as Sr or Pb, element concentrations, molecular markers, organic compound concentrations, and screening methods such as FTIR, NMR, untargeted metabolomics, etc. (e.g., [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]). For food, usually, the method of choice is the isotope analysis of the main elements, of which numerous studies have already been published (e.g., [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ], among many others).…”
Section: Introductionmentioning
confidence: 99%
“…(e.g., [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]). For food, usually, the method of choice is the isotope analysis of the main elements, of which numerous studies have already been published (e.g., [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ], among many others). However, in many cases, this method relies on databases containing the results of numerous authentic reference samples, to which unknown or questioned samples are compared.…”
Section: Introductionmentioning
confidence: 99%